2010
DOI: 10.1345/aph.1m289
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Stem Cell Mobilization Tactics

Abstract: The optimal mobilization strategy is still unknown; however, colony-stimulating factors remain the most commonly used mobilization agents. Currently, chemotherapy or plerixafor in combination with G-CSF is a reasonable option in heavily pretreated and hard-to-mobilize patients with non-Hodgkin's lymphoma and multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…G-CSF also has a favorable toxicity profile, with the most frequent adverse events being mild to moderate musculoskeletal pain (usually controlled with conventional analgesics), as well as dysuria, fever, headache, nausea and asymptomatic increase in alkaline phosphatase and gamma-glutamyl transferase. 48,49 Retrospective and prospective randomized studies suggest that the granulocyte--monocyte colony stimulating factor (GM-CSF) is less effective than G-CSF in mobilizing hematopoietic progenitor cells, either alone or in combination with chemotherapy, with an additional less favorable profile of safety and tolerability. 48,50 The combination of G-CSF and GM-CSF did not result in significant clinical benefits in comparison with isolated G-CSF.…”
Section: Measurement Of Cd34+ Cell Count In Peripheral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…G-CSF also has a favorable toxicity profile, with the most frequent adverse events being mild to moderate musculoskeletal pain (usually controlled with conventional analgesics), as well as dysuria, fever, headache, nausea and asymptomatic increase in alkaline phosphatase and gamma-glutamyl transferase. 48,49 Retrospective and prospective randomized studies suggest that the granulocyte--monocyte colony stimulating factor (GM-CSF) is less effective than G-CSF in mobilizing hematopoietic progenitor cells, either alone or in combination with chemotherapy, with an additional less favorable profile of safety and tolerability. 48,50 The combination of G-CSF and GM-CSF did not result in significant clinical benefits in comparison with isolated G-CSF.…”
Section: Measurement Of Cd34+ Cell Count In Peripheral Bloodmentioning
confidence: 99%
“…6 The combination of G-CSF with high-doses cyclophosphamide was shown to improve the efficiency of collection and increase the correlation between the CD34+ cell counts in peripheral blood and in the final collection. 8,49 Etoposide, in turn, has shown to be effective in the treatment of Hodgkin's and non-Hodgkin's lymphoma; thus, its inclusion in the mobilization regimens of patients with these tumors has the advantage of providing treatment during the mobilization phase 49 . The combination of vinorelbine and G-CSF is an excellent alternative in comparison with G-CSF alone or in combination with cyclophosphamide, showing a more favorable toxicity profile, resulting in earlier collection and lower costs.…”
Section: Measurement Of Cd34+ Cell Count In Peripheral Bloodmentioning
confidence: 99%
“…In a recently reported retrospective study of 2177 patients diagnosed with onco-hematological diseases, up to 60% of patients did not mobilize enough HSPC for an autologous transplant procedure [43]. Based on a review of clinical trials using chemotherapy, cytokines or combination regimens for mobilization of HSPC it was concluded that the optimal mobilization strategy is still unknown [41]. Thus, improving the strategies to boost HSPC mobilization could result in better transplantation outcomes.…”
Section: Mobilizationmentioning
confidence: 99%
“…Granulocytecolony stimulating factor (G-CSF, Filgrastim) and granulocyte macrophage (GM)-CSF (Sargramostim) are currently the only cytokines approved by the Food and Drug Administration (FDA) for HSPC mobilization, with G-CSF being the standard of care for initial mobilization therapy [40, 41]. HSPC from G-CSF-mobilized peripheral blood (mPB) engraft better than those from BM or umbilical cord blood (CB) and with fewer adverse reactions.…”
Section: Mobilizationmentioning
confidence: 99%
“…The hematopoietic progenitor cells are anchored in the BM by cytokines (such as CXCR4), which interact with SDF-1 (stromal cell derived factor-1, CXCL12) and adhesion molecules (such as very late antigen-1, VLA-1), which interact with vascular cell adhesion molecule-1. 69 During stem cell mobilization by G-CSF, the release of neutrophil proteases and the subsequent formation of a highly proteolytic environment in the BM results in the cleavage of these key molecules (mainly vascular cell adhesion molecule-1 and SDF-1). The interaction of HSCs with different types of stromal cells in the endosteal and endothelial niches not only has an important role in regulating HSC trafficking, but also affects their self-renewal, proliferation and differentiation capacity.…”
Section: Chemokine Axis Mobilizationmentioning
confidence: 99%